Implementation of Wireshark Application in Data Security Analysis on LMS Website - I Kadek Noppi Adi Jaya; Ida Ayu Utari Dewi; Gede Surya Mahendra (Information Technology and Science (ITScience), 2022)
Data security issues are an important aspect of data and information communication over networks. In addition, it is also necessary to look at the security side of the software. In addition to software, computers have an internet protocol in the form of HTTP which is commonly used to access websites. On the LMS website, students have access to lecture materials, discussion forums with lecturers and access to assignments given by lecturers. Wireshark is used to analyze network protocols, can log all packets going through and display detailed data. The purpose of this study is to use a Wireshark application to sniff LMS and pinpoint vulnerabilities in the system. The results of the sniffing process carried out using Wireshark on an LMS that uses the HTTP protocol clearly indicate the absence of encryption and expose the risk of vulnerabilities to the system. Recommendations given to LMS are the use of HTTPS protocol, implementation of Multi Factor Authentication, website log monitoring and password management. Recommended password management are periodic password changes, standardization policies for the use of characters in passwords and password hashing. It is hoped that when the recommendations are implemented it will improve security on the LMS website and reduce risks in data communications